Regional growth cycle synchronisation with the Euro Area - Gabriele Tondl; Iulia Traistaru-Siedschlag (The Economic and Social Research Institute (ESRI), 2006)
This paper investigates the patterns and determinants of the co-movement of economic activity between regions in the European Union and the Euro Area. Using a panel data of 208 EU-15 regions over the period 1989-2002 we estimate a system of four simultaneous equations to analyse the impact of regional trade integration, specialisation and exchange rate volatility on correlations of regional growth cycles with the Euro area. We find that deeper trade integration with the Euro area had a strong direct positive effect on the synchronisation of regional growth cycles with the Euro area. Industrial specialisation and exchange rate volatility were sources of cyclical divergence. Industrial specialisation had however an indirect positive effect on growth cycles synchronisation via its positive effect on trade integration, while exchange rate volatility had an indirect additional negative effect on growth cycle correlations by reducing trade integration. Industrial specialisation had an indirect negative effect on growth cycle correlations by increasing the exchange rate volatility. The direct impact of trade integration on growth cycle correlations was stronger in the pre-EMU sub-period, while in the EMU sub-period, the negative direct effects of industrial specialisation and exchange rate volatility were stronger than in the pre-EMU sub-period. A distinct result is the positive and significant relationship between exchange rate volatility and growth cycle correlations in the pre-EMU sub-period, suggesting that over this period, country-specific exchange rate fluctuations acted as shock absorbers. Our analysis is relevant in the context of the discussion about the macroeconomic adjustment to region-specific shocks in the European Monetary Union.
Keywords: E32; F33; F42; 330; European Monetary Union; Business Cycles; Regional Growth